SAD EMOTION IN JAVANESE LANGUAGE: AN ANALYSIS OF MEANING COMPONENT AND RELATION - Suswandi, Irwan; Widhyasmaramurti, .; WS, Afdol (PEOPLE: International Journal of Social Sciences, 2017)
Every human being has an emotive side that expressed through utterances of sentences. The utterances that produced are influenced by the culture of speakers of that language. Therefore a culture is usually influenced to human to represent the feelings of their language specific that implies through lexica. No exception to sad emotion. In the Javanese society that used Javanese language, there are vocabularies that contain diverse sad emotions. This study discusses sad emotion vocabulary in Javanese language. The data used come from Panjebar Semangat magazines. This study aimed to determine the words that contain a sad emotion in the Javanese language, along with the meaning components and meaning relations. There are three theories to analyze this study, namely theory of emotions and state of mindby Santangelo, theory of meaning component by Nida,and theory of meaning relation by Cruse. The method used in this study is a descriptive method. The results of this study are that (1) there are 15 vocabularies in the data that contain sad emotions, (2)there are 18 meaning components, and (3) there is indication of synonym relation between those 15 vocabularies.